PELATIHAN MODEL PEMBELAJARAN E-LEARNING BAGI GURU AL-FIRQOH AN NAJIAH YAYASAN MUJAHIDIN KABUPATEN MALANG - Mohammad Maskan; Achmad Suyono; Heru Utomo; Masitha Nisa Akmalia; Ika Kusumasasti (Jurnal Pengabdian kepada Masyarakat, 2024)
Current technological developments require human resources to keep up with the use of technology. One technological development that is widely used is information systems. An information system is a system within an organization that meets the needs of an electronic approach. Learning that originally used a manual approach changed to using electronics. Apart from that, the learning time is very flexible and the learning location does not have to be at school. junior high school and senior high school  Al Firqoh An Najiah's learning process is still classical. Electronic processes need to be used to optimize the learning process. With the existence of e-learning, learning will be more varied and will improve learning outcomes. The service aims to make it easier for teachers in the electronic learning process and enhance learning services for students to increase the achievement of learning outcomes using the RAD (Rapid Application Development) method, lecture methods, and training methods.